1987
DOI: 10.1172/jci112971
|View full text |Cite
|
Sign up to set email alerts
|

Steroid administration after myocardial infarction promotes early infarct expansion. A study in the rat.

Abstract: (4), a second possibility is that steroids lead to a prolonged phase during which "soft" necrotic myocardium thins and dilates. The third possibility is that steroids act solely by promoting the early expansion of freshly necrotic myocardium before collagen deposition begins. Infarct expansion, the thinning and dilatation of freshly infarcted myocardium that begins within the first few hours after transmural infarction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…One possibility is that the greater number of macrophages detected in healing post-MI scars of female animals during an inflammatory phase (Cavasin et al 2004) could underlie current observations, because macrophages facilitate inward remodeling in arterial vessels experiencing a reduction in blood flow (Bakker et al 2008). Such an assumption is also supported by the fact that the slightly higher fractional volume of mummified dead CM seen in post-MI scars of middle-aged male rats (as compared with females) may be a result of reduced macrophage response during MI healing similar to that observed in rats after inhibition of immune response with high doses of corticosteroids (Kloner et al 1978;Mannisi et al 1987) or in monocyte chemotactic protein 1-deficient mice showing an impeded phagocytic response (Dewald et al 2005).…”
Section: Effect Of Biological Sex On the Structural Composition Of A supporting
confidence: 60%
“…One possibility is that the greater number of macrophages detected in healing post-MI scars of female animals during an inflammatory phase (Cavasin et al 2004) could underlie current observations, because macrophages facilitate inward remodeling in arterial vessels experiencing a reduction in blood flow (Bakker et al 2008). Such an assumption is also supported by the fact that the slightly higher fractional volume of mummified dead CM seen in post-MI scars of middle-aged male rats (as compared with females) may be a result of reduced macrophage response during MI healing similar to that observed in rats after inhibition of immune response with high doses of corticosteroids (Kloner et al 1978;Mannisi et al 1987) or in monocyte chemotactic protein 1-deficient mice showing an impeded phagocytic response (Dewald et al 2005).…”
Section: Effect Of Biological Sex On the Structural Composition Of A supporting
confidence: 60%
“…Inhibition of this inflammatory response has been shown to impair wound healing and to induce severe consequences such as wall rupture [20,21]. Importantly, in our study, sPLA 2 -IIA inhibition by PX-18 did not result in reduced ventricular wall thickness, nor in aneurysmatic infarcts, indicating that wound healing was not impaired.…”
Section: Discussionmentioning
confidence: 41%
“…In our study, the increase in cell density in the infarct zone not accounted for by cell stretch would explain a decrease in wall thickness of approximately 12% and seemed to be largely due to the loss in intravascular volume. In a previous study with the same infarct model, 18 we found that the infarct zone increases in water content by about 6-7% in hearts 1 day after infarction, and it is possible that interstitial edema partially prevents the decrease in intercellular space produced by intravascular collapse. Consistent with this possibility is the observation in the present study that the nonvascular space between cells appeared to be slightly increased.…”
Section: Discussionmentioning
confidence: 57%
“…Approximately 11% of myocytes encountered were at or near branch points, and we used a method described previously to correct for branching. 18 The cell counts were performed twice for each region. In most cases, identical counts were obtained; however, if the two counts dilfered by more than 5%, cells were recounted another two times.…”
Section: Rat Infarct Modelmentioning
confidence: 99%